KOMITMEN KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA PERANGKAT DESA TREBUNGAN DAN DESA KAYUPUTIH DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING KABUPATEN SITUBONDO - Hosen, Toriq; Arief, Mohammad Yahya; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Quality human resources are people who can and are willing to help an organization achieve its goals. The aim of this research was to determine the increase in work commitment, work ability, organizational culture and human resource performance in Trebungan Village and Kayuputih Village. The population in this study were all Trebungan Village and Kayuputih Village officials, totaling 35 people. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing of this study used Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of testing the direct influence hypothesis using the Smart PLS 3.0 application showed that work commitment had a significant positive effect on organizational culture, work ability had a positive but not significant effect on organizational culture, work commitment had a significant positive effect on performance, work ability had a positive but not significant effect on performance, and organizational culture had a positive but not significant effect on performance. The results of testing the indirect influence hypothesis showed that the work commitment variable did not significantly influence performance through organizational culture, work ability did not significantly influence performance through organizational culture.